Batik Sebagai Salah Satu Media Komunikasi Dalam Upacara Adat Tradisi Jawa - Muhammad Arif Jati Purnomo (Ornamen, 2008)
As a social creature, man need of communication with another. The changing and developing of social role canâ€™t be separated with a well balanced communication factor between man with the creator, man with man, and man with another human beings.Batik as one of man cultural product is also the form of communication expression that learned by our parents through cloth media with resistance by using hot candle (malam) or using a tool called â€œcanthingâ€.The existance of Batik in Java canâ€™t be separated with a way of life, that believed its true by Javanese people. As people having local genius, Javanese people canâ€™t create Batik as one of visual communication media between Javanese people as cultural product creator with the creator as a source of all power. The creators of variety decoration of Batik, a long ago, not early created a beautiful in viewing thing but also gave a meaning that had a close relationship with their way of life. They created a decoration variation with a pure massage and a high hope. A hope that they wanted is by wearing Batik with certain motive is hoped it will bring a goodness and happiness for them. These are painted beautifully and symbolically and full of meaning.As a communication media of Javanese people, Batik can keep exist as one of cultural product that have a high praise and keep get a place in the people.Key words : Batik, culture product, communication